2016
DOI: 10.1111/chd.12353
|View full text |Cite
|
Sign up to set email alerts
|

School and Community Screening Shows Malawi, Africa, to Have a High Prevalence of Latent Rheumatic Heart Disease

Abstract: Malawi has a high rate of latent RHD, which is consistent with other results from sub-Saharan Africa. This study strongly supports the need for a RHD prevention and control program in Malawi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
38
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 23 publications
6
38
1
Order By: Relevance
“…In screening over 15,000 school children in Uganda, our team has detected a 3% prevalence of latent RHD 10, 11 . These findings have been replicated in other parts of Africa 12, 13 , Asia 14, 15 , South and Central America 8, 16 and the Pacific 1720 – uncovering a large population that may benefit from early detection.…”
Section: Introductionmentioning
confidence: 78%
“…In screening over 15,000 school children in Uganda, our team has detected a 3% prevalence of latent RHD 10, 11 . These findings have been replicated in other parts of Africa 12, 13 , Asia 14, 15 , South and Central America 8, 16 and the Pacific 1720 – uncovering a large population that may benefit from early detection.…”
Section: Introductionmentioning
confidence: 78%
“…Echocardiographic screening for RHD is superior to clinical screening alone which underestimates the burden of RHD. Since the standardization of criteria for echocardiographic screening of RHD by WHF, several studies have been done on school children in Africa and other regions. There are regional variations in prevalence of RHD as risk factors of the disease are largely socio‐economic in nature.…”
Section: Discussionmentioning
confidence: 99%
“…5 Likewise, a school screening echocardiographic study in India identified an odds ratio of 1.84 for females presenting with rheumatic heart disease, 6 and women were also disproportionately overrepresented in Indonesian and Ethiopian echocardiographic studies. 7,8 However, paediatric screening echocardiography programmes in Malawi, Senegal, Peru and the Northern Territory of Australia [9][10][11][12] have not identified significant gender differences in the burden of rheumatic heart disease. The reason for the different findings of each of these studies is not clear and may relate to the different ages of patients enrolled in each study, cultural patterns of medical referral and outreach in each country and varying use of WHO and World Heart Federation echocardiographic criteria for diagnosis of rheumatic heart disease.…”
Section: Discussionmentioning
confidence: 99%